The complete nucleotide sequence of the genome of Barley yellow dwarf virus-RMV reveals it to be a new Polerovirus distantly related to other yellow dwarf viruses - Krueger, Elizabeth N.; Beckett, Randy J.; Gray, Stewart M.; Miller, W. Allen (Frontiers in Microbiology, 2013)
The yellow dwarf viruses (YDVs) of the Luteoviridae family represent the most widespread group of cereal viruses worldwide. They include the Barley yellow dwarf viruses (BYDVs) of genus Luteovirus, the Cereal yellow dwarf viruses (CYDVs) and Wheat yellow dwarf virus (WYDV) of genus Polerovirus. All of these viruses are obligately aphid transmitted and phloem-limited. The first described YDVs (initially all called BYDV) were classified by their most efficient vector. One of these viruses, BYDV-RMV, is transmitted most efficiently by the corn leaf aphid, Rhopalosiphum maidis. Here we report the complete 5612 nucleotide sequence of the genomic RNA of a Montana isolate of BYDV-RMV (isolate RMV MTFE87, Genbank accession no. KC921392). The sequence revealed that BYDV-RMV is a polerovirus, but it is quite distantly related to the CYDVs or WYDV, which are very closely related to each other. Nor is BYDV-RMV closely related to any other particular polerovirus. Depending on the gene that is compared, different poleroviruses (none of them a YDV) share the most sequence similarity to BYDV-RMV. Because of its distant relationship to other YDVs, and because it commonly infects maize via its vector, R. maidis, we propose that BYDV-RMV be renamed Maize yellow dwarf virus-RMV (MYDV-RMV).